2021
DOI: 10.3390/cancers13153804
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Library Generation for Identification and Quantification of Endometrial Cancer Protein Biomarkers in Cervico-Vaginal Fluid

Abstract: Endometrial cancer is the most common gynaecological malignancy in high-income countries and its incidence is rising. Early detection, aided by highly sensitive and specific biomarkers, has the potential to improve outcomes as treatment can be provided when it is most likely to effect a cure. Sequential window acquisition of all theoretical mass spectra (SWATH-MS), an accurate and reproducible platform for analysing biological samples, offers a technological advance for biomarker discovery due to its reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The anatomical continuity of the uterine cavity with the lower genital tract has also led to interest in cervico-vaginal samples as a source of biomarkers for EC. Most of the literature around urogenital sampling for EC has involved cytological diagnosis, obtaining cytology samples from either the cervix or the uterine cavity directly, with mixed accuracy [ 114 ]. A recent study by O’Flynn et al reported a less invasive method of sampling using a Delphi screener, which does not require a full speculum examination, and reported pain scores similar to that of TVUS [ 112 ].…”
Section: He4 In Other Biofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomical continuity of the uterine cavity with the lower genital tract has also led to interest in cervico-vaginal samples as a source of biomarkers for EC. Most of the literature around urogenital sampling for EC has involved cytological diagnosis, obtaining cytology samples from either the cervix or the uterine cavity directly, with mixed accuracy [ 114 ]. A recent study by O’Flynn et al reported a less invasive method of sampling using a Delphi screener, which does not require a full speculum examination, and reported pain scores similar to that of TVUS [ 112 ].…”
Section: He4 In Other Biofluidsmentioning
confidence: 99%
“…However, due to its role in immunity, the levels may be affected by the vaginal microbiome at the time of sampling [ 113 ]. There have been no studies investigating vaginal HE4 as a potential biomarker for EC, although work in this area is underway [ 114 ].…”
Section: He4 In Other Biofluidsmentioning
confidence: 99%
“…To increase the signal-to-noise ratio when building bespoke spectral libraries from clinical samples several strategies can be employed. First, one may be able to adopt a pooling strategy, grouping the samples in sub-pools to increase the probability to detect low abundance proteins or putative “sample-specific proteins” as our group has previously undertaken in other studies [ 24 ]. However, this current study has been performed in serum samples and not in proximal fluids.…”
Section: Discussionmentioning
confidence: 99%
“…For both analyses, the TOF-MS mass range was 400–1250 Da, and the product ion mass range was 100–1500 Da [ 46 ]. Additionally, 5 µL (~1 μg) of each reconstituted sample was loaded on a 10 cm fused silica AcclaimTM PepMapTM 5 μm 100 Nano-Trap Column (Thermo Fisher Scientific, Loughborough, UK) using a U3000 RSLC high-pressure nanoLC (Dionex, Cambereley, UK) as described by Njoku et al Eluting peptides were quantified using a Thermo Scientific Orbitrap Fusion Lumos Tribrid mass spectrometer operating in DDA mode [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation